Establishing outcome-based curriculum: a triple helix partnership among Universities, Industries, and Government Agencies - Raharjo, Nuryadin Eko; Jaedun, Amat; Minghat, Asnul Dahar; Bahri, Nur Ayuni Shamsul; Mustakim, Siti Salina; Hastutiningsih, Arum Dwi (Jurnal Pendidikan Teknologi dan Kejuruan, 2025)
The Triple Helix Model (THM) of innovation has gained significant attention as a policymaking framework to enhance innovation and promote economic growth. This aligns with the principles of Outcome-Based Education (OBE), which focuses on clearly defined skills and knowledge that individuals are expected to acquire. This study aims to: (1) identify the THM model suitable for Indonesia and Malaysia; (2) describe the current level of THM implementation; (3) assess the THM ecosystem's needs from the perspectives of government, industry, and universities; (4) evaluate the role of the government in THM implementation; (5) assess the industry's role in THM; and (6) analyze the universities' role in THM. The research uses document analysis and Focus Group Discussions (FGD) involving lecturers, officials, and government personnel. Thematic analysis was applied to data from the document review and FGDs. A four-point Likert-scale questionnaire, based on the roles of key stakeholders in THM, was used, with data analyzed descriptively by Mean and Standard Deviation. The findings reveal that: (1) the Balanced Triple Helix Model (BTM) is the preferred model for both Indonesia and Malaysia; (2) the government, industry, and universities in both countries classify the BTM implementation as average; (3) the supporting ecosystem for BTM implementation is also classified as average; and (4) the roles of government, industry, and universities in both countries are classified as average in BTM implementation.Keywords: government, industry, OBE curriculum, Triple-helix model, university